Pendampingan Strategi Coping untuk Mengatasi Tingkat Stres pada Santri Baru di Pondok Pesantren Nurul Qur’an Pakunden Ponorogo - Ahmad Zainudin; Samsudin (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study comprehensively explores the phenomenon of academic stress and the coping mechanisms developed by students (santri) at Pondok Pesantren Nurul Qur'an, a traditional Islamic educational institution renowned for its intensive kitab kuning (classical Islamic texts) program. Employing a phenomenological qualitative approach, data were collected through semi-structured in-depth interviews with 56 male students aged 13–19 years. The findings reveal that the sources of academic stress are multidimensional, including strict memorization demands for nahwu and fiqh with daily targets, a competitive evaluation system, limited rest time due to the dense academic and religious schedule, and psychological pressure to meet expectations from both family and caregivers. Stress manifests in three main domains: physical (chronic fatigue, sleep disturbances), emotional (anxiety, irritability), and cognitive (memory decline, difficulty concentrating).The students developed dynamic and contextual coping strategies, categorized into three main patterns: (1) Religious-spiritual strategies, such as voluntary worship (tahajjud, fasting), dzikr, and tawakkul (trust in God); (2) Social strategies, including peer support systems and mentorship consultation; and (3) Cognitive-behavioral strategies, such as adaptive time management, self-reward, and simple relaxation techniques. The study also identifies unique protective factors within the pesantren environment, including the internalization of patience as a core value, role modeling by teachers (ustadz), and a positive doctrinal view of hardship in religious education. Policy recommendations include: (1) developing stress management modules based on pesantren values, (2) optimizing the counseling functions within pesantren, and (3) adjusting the evaluation system to better consider students’ mental health.